2017
DOI: 10.1088/1757-899x/219/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Observation of simultaneous increase in strength and ductility by grain refinement in a Fe-34.5Mn-0.04C steel

Abstract: Abstract. Fine grained Fe-34.5Mn-0.04C steel samples with fully recrystallized grain sizes of 3.8 to 2.0 µm were prepared by cold rolling followed by annealing a temperatures of either 650 °C or 800 °C . It is found that a simultaneous increase in both strength and ductility can be obtained by grain refinement, leading to an observation that the best combination of strength and ductility occurs in the sample with the finest recrystallized grain size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The joints were heat-treated in order to increase their corrosion resistance. This According to [14,[19][20][21], reduction in the grain size results in higher material ductility. In the analyzed cases, no monotonic relationship between the considered welding parameters (both travel and rotational speed) and the grain size was found, hence for the 800 and 1000 RPM rotational speed, the weld ductility was similar in each analyzed case.…”
Section: Effect Of Tool Rotation and Travel Speed On Joint Parametersmentioning
confidence: 99%
“…The joints were heat-treated in order to increase their corrosion resistance. This According to [14,[19][20][21], reduction in the grain size results in higher material ductility. In the analyzed cases, no monotonic relationship between the considered welding parameters (both travel and rotational speed) and the grain size was found, hence for the 800 and 1000 RPM rotational speed, the weld ductility was similar in each analyzed case.…”
Section: Effect Of Tool Rotation and Travel Speed On Joint Parametersmentioning
confidence: 99%
“…Most of the studies on ECAP were confined to soft metals and alloys with sufficient ductility. However, for hard‐to‐deform metals that have restricted independent slip systems, processing by ECAP results in occurrence of segmentation in which billets become sheared into discrete but interconnected segments …”
Section: Introductionmentioning
confidence: 99%
“…Different approaches has been proposed and applied to process hard‐to‐deform metals by ECAP. Several studies have demonstrated that sound specimens can be produced by elevating the pressing temperature . Nevertheless, it is shown that higher process temperatures lead to an increase in equilibrium grain size and fraction of low angle grain boundaries .…”
Section: Introductionmentioning
confidence: 99%